2018
DOI: 10.1055/s-0038-1670637
|View full text |Cite
|
Sign up to set email alerts
|

Apgar Scores at 10 Minutes and Outcomes in Term and Late Preterm Neonates with Hypoxic-Ischemic Encephalopathy in the Cooling Era

Abstract: In the cooling era, 47% of infants with no audible heart rate at 10 minutes and who were admitted to the neonatal intensive care unit survived; 24% without abnormalities on the brain MRI and 41% without severe abnormalities.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
12
3
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(22 citation statements)
references
References 28 publications
3
12
3
1
Order By: Relevance
“…This study demonstrated that infants with 10 min Apgar scores of zero who received therapeutic hypothermia in Japan were more likely to survive than those in recent studies performed in Western countries7–11 13; however, they were likely to develop neurodevelopmental disabilities identified after 18 months of age. Many infants in our cohort had severe neurodevelopmental disabilities and required chronic healthcare.…”
Section: Discussionmentioning
confidence: 55%
See 3 more Smart Citations
“…This study demonstrated that infants with 10 min Apgar scores of zero who received therapeutic hypothermia in Japan were more likely to survive than those in recent studies performed in Western countries7–11 13; however, they were likely to develop neurodevelopmental disabilities identified after 18 months of age. Many infants in our cohort had severe neurodevelopmental disabilities and required chronic healthcare.…”
Section: Discussionmentioning
confidence: 55%
“…Recent data in the era of therapeutic hypothermia7–10 have shown improved infant outcomes with 10-min Apgar scores of zero. Studies published after 2009, including observational series nested in therapeutic hypothermia randomised clinical trials and observational series of infants who received therapeutic hypothermia outside randomised clinical trials, showed that 44/90 (49%) term or near-term (>34 weeks of gestation) infants with Apgar scores of zero at 10 min survived and 22/90 (24%) survived without moderate or severe disabilities 7 11 12.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Apgar esta prueba no fue diseñada para predecir la salud, el comportamiento, la inteligencia, la personalidad o el resultado a largo plazo de un bebé (Ayrapetyan et al, 2018). Fue diseñado para ayudar a los proveedores de atención médica a determinar la condición física general de un recién nacido para que puedan decidir rápidamente si el bebé necesita atención médica inmediata.…”
Section: Materiales Y Métodounclassified